Pengaruh Diameter Elemen Bara Api Terhadap Peningkatan Efisiensi Kompor LPG - Fadelan, Fadelan; Sudarno, Sudarno (Semesta Teknika, 2017)
Â The addition of embers is an effort to improve the efficiency of LPG stoves. Fire-embossed element of woven pattern is made of wire nikelin. The device when is burned with LPG cooker fire will incite to form a high-temperature fire, so as to burn the unperfectly burned fuel vapor around the wire. Previous research has shown that the element of fire can improve the efficiency of 8.32%. The efficiency test is done by boiling water test. The diameter of the embers element is varied, 20 mm, 30 mm, and 40 mm. The performance of the appliance is compared to the LPG stove without the use of embers. Temperature distribution at each treatment was also examined. It was found that the use of fire element with diameter of 0.20 mm resulted in the highest efficiency of 61.71%, with an increase of 8.32%. Temperature distribution test results show that the use of fire diameter element 0.20 mm produce the most optimal adult fire areas.